PENATALAKSANAAN FISIOTERAPI PADA KASUS TENDINITIS SUPRASPINATUS SINISTRA DENGAN MODALITAS ULTRASOUND, TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DAN TERAPI LATIHAN DI RSUD KRATON KABUPATEN PEKALONGAN - Yayang Yuliana Cipta; Eko Budi Prasetyo (LPPM Universitas Pekalongan, 2020)
Background : Supraspinatus Tendinitis is inflammation of the supraspinatus tendon due to repeated friction of the tendon for a long time. Supraspinatus Tendinitis occurs at the age of 30-70 years, 20% to 33% in the adult population. The problem of physiotherapy in the case of Supraspinatus Tendinitis is the presence of muscle spasm, tenderness and motion pain, limitation of LGS, decreased muscle strength and decreased functional activity. In the case of Supraspinatus Tendinitis the modalities used are Ultrasound, TENS and Exercise Therapy.Objective : To determine the effect of Ultrasound, TENS and Exercise TherapyMethod : Research with descriptive analytical method. The method of collecting data uses the Autoanamnesis method. The research design used was a case study. The subjects of this study were patients with Supraspinatus Tendinitis using research instruments to examine spasm, pain, muscle strength, scope motion of joint (LGS), and functional activity.Results : From the therapy 6 times the results were obtained: (1) There was a decrease in muscle spasm at T1 = 1 to T6 = 0, (2) There was a decrease in tenderness at T1 = 6 to T6 = 2, and motion T1 = 6 to T6 = 3 , (3) There is an increase in muscle strength T1 = 4 to T6 = 5, (4) There is an increase in LGSactive flexion movement T1 = 105º to T6 = 120º, in abduction T1 = 90º to T6 = 120º, and LGS passive to flexion motion T1 = 135º becomes T6 = 145º, and in abduction T1 = 115º becomes T6 = 130º, (4) There is an increase in functional activity with a total score of T1 = 60 (moderate dependence) to T6 = 33 (mild dependence).Conclusion : Physiotherapy with Ultrasound, TENS and Exercise Therapy Interventions can reduce the problems that arise in the condition of Supraspinatus Tendinitis.Suggestion : Know more deeply about the condition of Supraspinatus Tendinitis